Utility of Intravascular Ultrasound in Peripheral Vascular Interventions: Systematic Review and Meta-Analysis. (July 2020) - Sheikh, Azfar Bilal; Anantha-Narayanan, Mahesh; Smolderen, Kim G.; Jelani, Qurat-Ul-Ain; Nagpal, Sameer; Schneider, Marabel; Llanos, Fiorella; Ionescu, Costin; Regan, Christopher; Attaran, Robert; Altin, S. Elissa; Mena-Hurtado, Carlos
Objectives: We sought to compare outcomes between intravascular ultrasound– (IVUS) versus angiography (AO)-guided peripheral vascular interventions (PVIs). Introduction: Intravascular ultrasound facilitates plaque visualization and angioplasty during PVIs for peripheral arterial disease. It is unclear whether IVUS may improve the durability of PVIs and lead to improved clinical outcomes. Methods: This is a study-level meta-analysis of observational studies. The primary end points of this study were rates of primary patency and reintervention. Secondary end points included rates of vascular complications, periprocedural adverse events, amputations, technical success, all-cause mortality, and myocardial infarction. Results: Eight observational studies were included in this analysis with 93 551 patients. Mean follow-up was 24.2 ± 15 months. Intravascular ultrasound–guided PVIs had similar patency rates when compared with AO-guided PVIs (relative risk [RR]: 1.30, 95% confidence interval [CI]: 0.99-1.71, P = .062). There was no difference in rates of reintervention in IVUS-guided PVIs when compared to non-IVUS-guided PVIs (RR: 0.41, 95% CI: 0.15-1.13, P = .085). There is a lower risk of periprocedural adverse events (RR: 0.81, 95% CI: 0.70-0.94, P = .006) and vascular complications (RR: 0.81, 95% CI: 0.68-0.96, P = .013) in the IVUS group. All-cause mortality (RR: 0.76, 95% CI: 0.56-1.04, P = .084), amputation rates (RR 0.83, 95% CI: 0.32-2.15, P = .705), myocardial infarctions (RR: 1.19, 95% CI: 0.58-2.41, P = .637), and technical success (RR: 1.01, 95% CI: 0.86-1.19, P = .886) were similar between the groups. Conclusions: Intravascular ultrasound–guided PVIs had similar primary patency and reintervention when compared with AO-guided PVIs with significantly lower rates of periprocedural adverse events and vascular complications in the IVUS-guided group.